Performance evaluation of a capacity-regulated high temperature heat pump for waste heat recovery in dyeing industry. (25th January 2016) - Wu, Xiaokun; Xing, Ziwen; He, Zhilong; Wang, Xiaolin; Chen, Wenqing
Highlights: A capacity regulated HTHP system was developed for waste heat recovery. Dyeing liquid temperature rising rate was accurately controlled at 0.6–2.5 °C/min. The HTHP system could be reliably operated at different heat source temperatures. The highest dyeing liquid temperature could reach 95 °C with an average COP of 4.2. Abstract: In this paper, a capacity-regulated high temperature heat pump (HTHP) system using a twin-screw compressor was designed to recover waste heat in dyeing industry. The performance of the HTHP system was investigated under an on-site skein dyeing process condition. Results showed that the HTHP system could effectively utilize the waste heat at different temperatures to provide the energy required by the dyeing process. The heating capacity of the HTHP system could be well controlled to achieve the desired dyeing liquid temperature rising rate between 0.6 and 2.5 °C/min during different heating processes. The on-site testing results further demonstrated that the HTHP system could be reliably operated to heat the dyeing liquid temperature up to 95 °C with an average system COP of 4.2 during the entire heating process. Economic analysis indicated that the HTHP system could save about 47% of the operating cost in comparison to the traditional steam heating.